Reconsidering “The inappropriateness of conventional cephalometrics” - Bookstein, Fred L. (Am J Orthod Dentofacial Orthop, 2016)
Of all the articles on cephalometrics published in the AJO-DO during the last half-century, the one most cited in the scientific literature is the 1979 article, “The inappropriateness of conventional cephalometrics,” by Robert Moyers and me. The durable salience of this article is perplexing; its critique was misdirected (it should have been aimed at the craniometrics of the early twentieth century, not merely the roentgenographic extension used in the orthodontic clinic), and its proposed remedies have all failed to establish themselves as methods of any broad utility. When the problems we highlighted have been resolved at all, the innovations that resolved them owe to tools very different from those we suggested and were imported from fields quite a bit farther from biometrics than we expected back in 1979. One of these tools was the creation de novo of a new abstract mathematical construction, statistical shape space, in the 1980s and 1990s; another was a flexible and intuitive new graphic, the thin-plate spline, for meaningfully and suggestively visualizing a wide variety of biological findings in these spaces. On the other hand, many of the complaints Moyers and I enunciated back in 1979, especially those stemming from the disarticulation of morphometrics from the explanatory styles and purposes of clinical medicine, remain unanswered even today. The present essay, a retrospective historical meditation, reviews the context of the 1979 publication, its major themes, and its relevance today. This essay is dedicated to the memory of Robert E. Moyers on the 100th anniversary of the American Journal of Orthodontics and Dentofacial Orthopedics.